Kualitas Pelayanan Dan Kompetensi Pegawai Kecamatan Penajam Kabupaten Penajam Paser Utara - Andi Murni; Nurmadhani Fitri; Mulyadi Hamid (Journal of Management and Social Sciences, 2024)
This research aims to determine the quality of service for employees in Penajam District, North Penajam Paser Regency and determine the competency of employees in Penajam District, North Penajam Paser Regency. The research method used is a qualitative method. The number of informants was 12 people consisting of 6 sub-district officials and 6 community members. The results of the research show that the quality of service for employees in Penajam District, North Penajam Paser Regency is satisfactory and to improve quality you must pay attention to factors inhibiting and supporting public services, paying attention to procedures for providing services to the community. The competency of Penajam District Employees, North Penajam Paser Regency is quite good and must continue to be improved.